2023
DOI: 10.1001/jamaoto.2022.3652
|View full text |Cite
|
Sign up to set email alerts
|

Increased Delay in Diagnosis, but Not Treatment, Among Patients With Oral Cancer During the COVID-19 Pandemic

Abstract: This retrospective cohort study assesses delays in diagnosis and treatment for patients with oral squamous cell carcinoma in a tertiary care University Hospital in Naples, Italy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…This kind of evidence should be considered with the scarcity of papers that evaluate this kind of multidisciplinary approach and the possible collaboration between these two specialists [29][30][31]. The lack of scientific papers evaluating the important relationship between therapies and outcomes with such multidisciplinary approach should be further analyzed and studied including besides this epidemiological evaluation of clinical studies with long-term follow-up [32,33].…”
Section: Collaboration Landscape: Speech Language Therapistsmentioning
confidence: 99%
“…This kind of evidence should be considered with the scarcity of papers that evaluate this kind of multidisciplinary approach and the possible collaboration between these two specialists [29][30][31]. The lack of scientific papers evaluating the important relationship between therapies and outcomes with such multidisciplinary approach should be further analyzed and studied including besides this epidemiological evaluation of clinical studies with long-term follow-up [32,33].…”
Section: Collaboration Landscape: Speech Language Therapistsmentioning
confidence: 99%
“…Several studies have reported disparities associated with access to care during the COVID-19 pandemic, which may have affected stage at presentation and survival outcomes of patients with cancer, especially among individuals with limited access to care . However, although studies have described the epidemiology and outcomes of HNC associated with the COVID-19 pandemic, the generalizability of these studies to the HNC population in the US has been limited, as most have been either from a single institution, aggregated data from multiple institutions, or studies with data outside of the US . Thus, because of the lack of population-based data, whether or to what extent the COVID-19 pandemic affected diagnoses of HNC in the US is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12] However, although studies have described the epidemiology and outcomes of HNC associated with the COVID-19 pandemic, the generalizability of these studies to the HNC population in the US has been limited, as most have been either from a single institution, aggregated data from multiple institutions, or studies with data outside of the US. 7,9,[13][14][15][16][17][18][19] Thus, because of the lack of population-based data, whether or to what extent the COVID-19 pandemic affected diagnoses of HNC in the US is unclear. Also, the understanding of population-based changes in the stage of presentation of HNC during the COVID-19 pandemic is limited.…”
mentioning
confidence: 99%
“…However, relatively few studies have attempted to estimate the actual delay experienced by individual patients. The compensation effects of system adaptation on resource capacity (e.g., adjustment of treatment regimen/protocols) by oncologists might have resulted in more personalized treatments without lengthening their delays during the COVID-19 pandemic, as shown in several cancer types [19,20]. To date, real-time data on this aspect is still scarce.…”
Section: Introductionmentioning
confidence: 99%